Store-operated calcium entry facilitates LPS-induced superoxide anion-dependent macrophage extracellular traps - Thang Ngoc Nguyen; Tzu‐Chien Lin; Waratchaya Chimphlee; Kon Xuen Siew; Naphatsawan Vongmanee; Shih‐Chuan Hsiao; Sarinporn Visitsattapongse; Wen‐Tai Chiu (Open Biology, 2025)
-mediated regulation of NOX plays a crucial role in METosis, especially in SOCE, and provides novel ideas for future research.
Keywords: Neutrophil, Myeloperoxidase and Oxidative Mechanisms; Nitric Oxide and Endothelin Effects; Immune cells in cancer